Lossless Kerr-phase gate in a quantum-well system via tunneling interference effect for weak fields - Shi, YL; Huang, YC; Wu, JX; Zhu, CJ; Xu, JP; Yang, YP (American Physical Society, 2015)
We examine a Kerr phase gate in a semiconductor quantum well structure based on the tunnelling interference effect. We show that there exist a specific signal field detuning, at which the absorption/amplification of the probe field will be eliminated with the increase of the tunnelling interference. Simultaneously, the probe field will acquire a -π phase shift at the exit of the medium. We demonstrate with numerical simulations that a complete 180^° phase rotation for the probe field at the exit of the medium is achieved, which may result in many applications in information science and telecommunication.